Individual, group, and temporal perspectives on the link between wealth and realistic threat - Celikkol, Göksu (2022)
In this 28-country study (N = 6112), we assessed how subjective perceptions and objective indicators of wealth were associated with majority group members’ perceptions of realistic threat related to immigration. Subjective wealth was assessed by individuals’ perceptions of their personal wealth (current/anticipated) and of their coun- try ́s wealth, whereas objective country-level wealth was assessed by GDP and HDI. Multilevel analyses showed that living in a country with a lower objective wealth and perceiving the country’s relative wealth as low were associated with higher levels of perceived realistic threat. We also found that an anticipated decrease in personal wealth in the future was associated with higher threat perceptions only in low HDI countries. Our results suggest that perceived realistic threat is fostered by a perceived decline in the current wealth of the country, and country-level wealth may play a role in calibrating threat responses to anticipated personal wealth